Implementing Safe and Effective Pediatric Procedural Sedation in the Emergency Department. (October 2021) - Jordan, Kathleen S.; Steelman, Sara H.
Abstract : There has been a great increase in the number of diagnostic and therapeutic procedures performed in the emergency department (ED) setting over the past several decades. Most of these procedures are unscheduled, unplanned, and much more likely to be successful and result in a positive outcome when the child's pain, fear, anxiety, and movement are controlled. To promote patient quality and safety, increase the effectiveness and efficiency of care, and improve patient and caregiver satisfaction, there has been a proportionate increase in the number of pediatric procedural sedations performed in the ED. With proper education and skills verification, pediatric procedural sedation can be safely and efficaciously performed in the ED. The purpose of this article is to present an overview of pediatric analgesia, anxiolysis, and sedation to promote compassionate, evidence-based emergency care of children and optimize procedural performance and outcomes.